Building a Stronger Case for Independent Reading at School - Adriana G. Bus; Yi Shang; Kathleen Roskos (SAGE Publishing, 2024)
The effectiveness of incorporating independent reading practice in schools has long been a subject of uncertainty. To shed light on this ongoing debate, this meta-analysis seeks to investigate the impact of in-school independent reading on three crucial measures-attitudes toward reading, word recognition, and comprehension-focusing on K-10 students. The analysis encompasses (quasi-)experimental studies conducted between 1970 and 2020, examining a total of 7,493 students across 47 studies. Because most studies contain more than one outcome measure or effect size, we used a meta-analytic model with a three-level structure. The findings reveal a statistically significant overall effect size (Hedges' g = .08). Specifically, the effect sizes are more pronounced when considering word recognition (i.e., word attack, word identification, decoding, and fluency; Hedges' g = .21) and students' reading attitude (Hedges' g = .18) as outcome measures. However, the effect size for comprehension-the most commonly assessed outcome measure-was approximately zero (Hedges' g = −.014).